A philosophical analysis of the role of indigenous religion in the growth and expansion of Christianity in Africa (2019)
Religion plays a dominant role in the life of the average African. Long before the advent of Christianity, Africans have been actively practising their indigenous religion. Several scholars have focused on various aspects of the history of Christianity in Africa with little attention paid to the contributions of the Indigenous religion to Christianity, especially in the area of its growth and expansion. This paper seeks to address this lacuna with the view to providing answers to questions on the influences of the indigenous religion of the people on Christianity in Africa. The interaction of Christianity with the indigenous religion often leads to the attitude of skepticism, especially in Christian circles. Contrary to the erroneous belief that African indigenous religion is anti-Christianity, it has actually contributed to its growth and expansion in Africa. This study adopts Descartes ’s methodological skepticism which has its roots in epistemology, in its analysis of the contributions of the Indigenous religion to Christianity.